Answer:
According to the Law of Absorption, these 2 expressions are equivalent:
p ∨ (p ∧ q) = p
Truth Table:
(see the image attached)
Explanation:
To construct the Truth Table you can consider the 4 possible combinations of states that p and q could have, that is
1. p=T, q=T
2. p=T, q=F
3. p=F, q=T
4. p=F, q=F
Then you can calculate p ∨ (p ∧ q) = p for each combination
1. T ∨ (T ∧ T) = T
2. T ∨ (T ∧ F) = T
3. F ∨ (F ∧ T) = F
4. F ∨ (F ∧ F) = F
You can see that the previous values are the same states that p has, you can also see it in the table attached.